The role of agricultural sector in food security and poverty alleviation in Indonesia and Turkey - Imam Mukhlis; Ozlem Sokmen Gurcam (INOVASI, 2022)
This study aims to analysis the role of agricultural sector in food security and poverty alleviation in Indonesia and Turkey. Data analysis method was descriptive data analysis,while the data were secondary data. The results of this study show that Indonesian agricultural sector provides basic food needs for the population in the form of rice, corn, and cassava productions. When considered in terms of Turkey, agricultural sector shows that products such as wheat,sugar beet and barley provide the basic food needs for the population.In some cases where food needs cannot be fulfilled by domestic productions, importing food products from other countries becomes an option. Import is expected to be able to maintain the stability of domestic food price and availability. In addition, agricultural sector plays a role in providing employment and income for the population in Indonesia and Turkey. By doing this, agricultural sector can provide food and alleviating poverty in both countries.